Ortho-nitrobenzyl derivatives as potential anti-schistosomal agents (Brazilian Journal of Pharmaceutical Sciences, 2018)
In the search for new anti-schistosomal agents, a series of fifteen ortho-nitrobenzyl derivatives was assayed in vitro against both the schistosomulum (somule) and adult forms of Schistosoma mansoni. Compounds 8 and 12 showed significant activity against somules at low micromolar concentrations, but none was active against adults. The SAR demonstrated that the compounds most active against the parasite were mutagenic to the human cell line RKO-AS45-1 only at concentrations 10- to 40-fold higher than the worm-killing dose. Given their electrophilicity, compounds were also screened as inhibitors of the S. mansoni cysteine protease (cathepsin B1) in vitro. Amides 5 and 15 exhibited a modest inhibition activity with values of 55.7 and 50.6 % at 100 µM, respectively. The nitrobenzyl compounds evaluated in this work can be regarded as hits in the search for more active and safe anti-schistosomal agents.